Identification and Susceptibility of Aspergillus Section Nigri in China: Prevalence of Species and Paradoxical Growth in Response to Echinocandins - Li, Yali (J Clin Microbiol, 2015)
Molecular identification and in vitro antifungal susceptibility tests of 43 Aspergillus section Nigri isolates from China were performed. Aspergillus niger and Aspergillus tubingensis were present in almost equal numbers. All of the isolates had low MIC/MECs (minimum effective concentrations) for the 7 common antifungals, and a paradoxical effect was observed for the first time in response to caspofungin and micafungin.